1994
DOI: 10.1080/00223980.1994.9712719
|View full text |Cite
|
Sign up to set email alerts
|

Does Personality Influence Brand Image?

Abstract: Consumer psychologists have attempted to relate purchase behavior, media choice, innovation, segmentation, and a wide variety of other marketing variables to consumer personality. Results of these studies have been mixed with most studies demonstrating a weak relationship between consumer personality and market behavior. The purpose of the present study was to explore the relationship between human personality using the Myers-Briggs Type Indicator and product personality. To date, the MBTI has not been applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 24 publications
3
30
0
1
Order By: Relevance
“…Dolich, 1969;Hamm and Cundiff, 1969;Shank and Langmeyer, 1994;Vitz and Johnston, 1965), we expect that consumers with different personality types would prefer brands with personalities that match their own. In the current study we have tested 15 propositions concerning a match between brand personality dimensions and the DI types, as a proxy of human personality types, in an effort towards providing a systematic approach for the analysis of human-brand personality match.…”
Section: Resultsmentioning
confidence: 99%
“…Dolich, 1969;Hamm and Cundiff, 1969;Shank and Langmeyer, 1994;Vitz and Johnston, 1965), we expect that consumers with different personality types would prefer brands with personalities that match their own. In the current study we have tested 15 propositions concerning a match between brand personality dimensions and the DI types, as a proxy of human personality types, in an effort towards providing a systematic approach for the analysis of human-brand personality match.…”
Section: Resultsmentioning
confidence: 99%
“…The identification of the brand personality's antecedents, which have received significant attention but limited empirical testing (Aaker, 1997), would provide both theoretical and practical implications for advertising scholars and practitioners. Another reasonable suggestion is that over time the entire mix of marketing communication variables and every other exposure that the brand receives creates a brand personality (Shank & Langmeyer, 1994). Advertising, along with other forms of marketing communications, is an undeniable force in creating brand personality and image.…”
Section: Future Researchmentioning
confidence: 99%
“…Since the brand's personality is created and developed by any direct or indirect brand contact that the consumer experiences (Shank & Langmeyer, 1994;Plummer, 1985), it is essential for consumers to experience the brand first before they form any subjective perceptions about and personality characteristics associated with the brand. The effect of such experiences is the creation of a brand with a personality of its own.…”
Section: Theoretical Background Brand Personalitymentioning
confidence: 99%
“…Research in the field of consumer behavior has looked at how brand personality allows the consumer to express the image that he or she has of himself or herself (Ferrandi, Merunka, Valette-Florence, & De Barnier, 2002). Shank and Langmeyer (1994) showed that perceived brand personality can go farther still and be independent of consumer personality, because individuals with very different personalities see the product or brand personality in a similar way. A recent study, which focuses on the gender aspects (masculine/feminine) of brand personality, shows that when there is congruence between perceived brand personality and the selfconcept of the consumer, responses are more positive when it comes to a favorable attitude to the brand, preference for the brand over competing brands, a high level of affection and trust, and a high degree of loyalty to the brand in terms of attitude and behavior (Grohmann, 2009).…”
Section: Antecedents and Effects Of Brand Personalitymentioning
confidence: 99%